Linking Goal Orientation and Resilience to Academic Integrity through Behavioral Learning - Fitriah M. Suud; Mirawati Mirawati; Nurul Asmaa Akmal Binti Md Din; Faisal Bin Husen Ismail; Abd Razak Bin Zakaria; Kasmil S. Abdulwahid (SCAD Independent, 2026)
Academic integrity remains a persistent challenge in higher education, particularly within learning environments characterized by performance pressure and diverse socio-cultural contexts. This study examines how goal orientation and academic resilience shape academic integrity through the mediating role of behavioral learning among university students in Malaysia and the Philippines. Using a quantitative cross-sectional design, data were collected from 326 undergraduate students across three universities and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The findings demonstrate that both goal orientation and academic resilience exert significant positive effects on behavioral learning and academic integrity. Behavioral learning was confirmed as a key mediating mechanism through which psychological dispositions are translated into ethical academic conduct. Cross-national analysis further reveals contextual variation: in Malaysia, structured learning systems and strong institutional regulation amplify the role of behavioral learning, whereas in the Philippines, academic resilience plays a more prominent role in sustaining academic integrity. These results contribute to a process-oriented understanding of academic integrity and underscore the importance of context-sensitive, learning-centered strategies in promoting ethical academic behavior in higher education.